JURIDICAL ANALYSIS OF CREDIT AGREEMENTS WITH MORTGAGE GUARANTEE AND CESSIE REQUIRED AS GUARANTEE AT PT. BRI AGRO NIAGA PEKANBARU - BR Napitupulu, Maria; Saidin, Saidin; Maharany Barus, Utary; Sinaga, Henry (RADJA PUBLIKA, 2022)
Banking institutions have an important role in economic development with lending activities regulated in credit agreements. In the credit agreement between PT. BRI Agro Niaga Pekanbaru and PT. Sipakko Jaya Abadi with PTPN V there are efforts to secure credit with collateral and cessie required as collateral. This study uses empirical normative legal research methods. The data used include primary, secondary and tertiary data. Collecting data using library research and field research with interviews. Furthermore, the data were analyzed using qualitative data analysis methods. The results of the study indicate that the credit agreement between PT. BRI Agro Niaga Pekanbaru and PT. Sipakko Jaya Abadi has complied with the legal basis in force in Indonesia and the legal relationship that exists between PT. BRI Agro Niaga Pekanbaru as creditor and PT. Sipako Jaya Abadi as the debtor with PTPN V as the third party is PT. Sipakko Jaya Abadi entered into a credit agreement with PT. BRI Agro Niaga Pekanbaru with the aim of financing the work contract with PTPN V. The implementation of the Mortgage Guarantee with the required cessie as collateral is not in accordance with the legal basis and because essentially the cessie is a transfer of receivables. The execution of the guarantee in the credit agreement cannot be carried out on the cessie required as collateral.